STRATEGI PENGEMBANGAN BAHAN AJAR PENDIDIKAN AGAMA KATOLIK PADA KONDISI PENDIDIKAN DI DAERAH TERTINGGAL - Marsianus Reresi; Vinsensius Bawa Toron; Paula Rawul (STP Reinha Larantuka, 2023)
This research is a library research that aims to analyze and describe the strategy for developing teaching materials for Catholic Religious Education in underdeveloped areas. The research method used is descriptive research. The author uses descriptive research with an emphasis on the power of analysis of sources and available data to be interpreted and described which leads to a focus discussion. The results of the study found that the condition of education in underdeveloped areas requires more teaching materials with self-instructional characteristics which are packaged in small/specific activity units, with easy-to-understand language, containing examples or illustrations, practice questions and material summaries as well as assessment instruments. Therefore an PAK teacher in developing teaching materials needs to start from an analysis of the needs and characteristics of students and choose the type of printed teaching materials which can be in the form of comic Pop-up books by highlighting local wisdom and natural media.